ACCESS TO JUSTICE IN ENVIRONMENTAL MATTERS: COMPARATIVE STUDY OF INDIA AND EU (UKLO Proceedings, 2026)
Introduction: In environmental governance, access to justice is crucial to ensure accountability, public contribution and safeguards of rights. Both India and Europe have established legal systems to uphold environmental justice, but they do so within very different legal, cultural and constitutional frameworks.  The Aarhus Convention dominates the European framework, although “Articles 21, 32 and 226 of the Indian Constitution” are based on judicial activism and constitutional foundations. This study examines the similarities, differences and lessons for improving access to justice between the judicial systems of India and Europe. Method: The study adopts comparative legal analysis referring to international instrument’s constitutional provisions and judicial decisions. Decisions of the “Indian Supreme Court and the National Green Tribunal (NGT)” are analyzed alongside decisions of the “European Court of Justice (ECJ) and European domestic courts.”Result: The Indian judiciary has given a wide interpretation to the right to a healthy environment under Article 21, thereby expanding “access to justice via PILs (PILs).” A special place for environmental disputes has also been bestowed by the NGT. On the other hand, Aarhus Convention guarantees that people and NGOs can challenge environmental decisions in Europe. Although the ECJ has upheld these rights, member countries continue to impose practical barriers such as cost and permanency requirements.Discussion: While both countries support the right to access to justice, Europe places greater emphasis on procedural safeguards and conformity to international standards, while India relies more on “fundamental rights and judicial innovation.” Europe offers organized but sometimes limited procedural channels, while India’s PIL mechanism offers a comprehensive approach but risks overburdening the courts. Collectively, these models demonstrate different but complementary perspectives on environmental justice.